The Expansion of Latifundio in the Bolivian Altiplano - Rivera Cusicanqui, Silvia (1979)
This work is a preliminary elaboration of the data obtained in an investigation carried out in Bolivia between March and October 1977. Before entering the subject, we will briefly present the main changes in the economic structure of the country, focusing on the period 1870-1920. Then we will expose some hypotheses about the "articulation" between feudalism and capitalism. In what constitutes the heart of the work, we will analyze the processes of expropriation of communal property that occurred between 1866-1869 and 1881-1920, stopping at the social composition of the landowner sector and the peculiar structure of their economic interests, to finally arrive at some tentative conclusions.